Zambia : 2009 Article IV Consultation, Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Modification of Performance Criteria; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Zambia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This 2009 Article IV Consultation highlights that the Zambian economy has performed well in recent years and showed some resilience to the recent global recession. Growth in 2009 is now projected at 5.3 percent, in line with the average for recent years, as the slowdown in the tertiary sector was compensated by a significant increase in copper production and a bumper crop. Executive Directors have commended the Zambian authorities for their prudent macroeconomic management, observing that the Zambian economy has proven resilient to the global economic crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet